Water Quality and Status Aquatic Fauna of Dhaka Mega City, Bangladesh - Nur Hussain (Program Pascasarjana Universitas Sriwijaya, 2018)
This research focused of the effect of water pollution on aquatic fauna at Dhaka mega city, Bangladesh. Dhaka is an over populated capital city of Bangladesh. The rapid urban expansion, highly demographic growth, industrial development of this mega city have been including in a polluted city. The industrial and municipal waste material have polluted the wetlands basin of this city. Aquatic fauna of these wetlands basin are endanger for pollutant substances. The aquatic records and have been collected by field observation. The water quality of this mega city have been explored by sample collection and lab analysis. Dissolved Oxygen (DO), Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) are less than standard level. As a result the water body fully toxic that condition is not free for living organism. On the other way, the availability of Total Dissolved Solids (TDS), Lead (Pb) and Cadmium (Cd) are catastrophically high from standard level. So the water quality fully polluted and it is not sustainable for aquatic fauna.